2009
DOI: 10.1002/ab.20279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of realism on extended violent and nonviolent video game play on aggressive thoughts, feelings, and physiological arousal

Abstract: Previous research has shown that playing violent video game exposure can increase aggressive thoughts, aggressive feelings, and physiological arousal. This study compared the effects that playing a realistic violent, unrealistic violent, or nonviolent video game for 45 min has on such variables. For the purpose of this study, realism was defined as the probability of seeing an event in real life. Participants (N 5 74; 39 male, 35 female) played either a realistic violent, unrealistic violent, or nonviolent vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 29 publications
1
48
1
5
Order By: Relevance
“…Nelson et al [41,57,58] found that short-term game exposure did appear to produce strategy changes [10]. But some researchers claimed that they offered solid evidences that the video game had an increase in cognitive performance both in short term and long term [6,51]. This is an important question that should be made clearly in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nelson et al [41,57,58] found that short-term game exposure did appear to produce strategy changes [10]. But some researchers claimed that they offered solid evidences that the video game had an increase in cognitive performance both in short term and long term [6,51]. This is an important question that should be made clearly in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on video games so far has mainly focused on their negative effects, such as the addiction [2][3][4][5][6][7] caused by games violence. There are now many studies looking at what is called pathological gaming or video game "addiction".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adults, interestingly, the more the game pertains to the real life situation, the more the players display aggressive thoughts and attitudes, and physiological arousal. Such effects are seen as quickly as 45 min into the play (Barlett & Rodeheffer, 2009). The studies which pertain to the detrimental influence of games on behavior are however riddled with controversies stemming mostly from inadequate methodological issues.…”
Section: Introductionmentioning
confidence: 98%